The archaeology of the Holy Land : from the destruction of Solomon's Temple to the Muslim conquest - Magness, Jodi (Cambridge University Press, 2012)
"In the heart of the ancient Near East (modern Middle East) and at a crossroads between once mighty powers such as Assyria to the east and Egypt to the south is a tiny piece of land -- roughly the size of New Jersey -- that is as contested as it is sacred. One cannot even name this territory without sparking controversy. Originally called Canaan after its early inhabitants (the Canaanites), it has since been known by various names. To Jews this is Eretz-Israel (the Land of Israel), the Promised Land described by the Hebrew Bible as flowing with milk and honey. To Christians it is the Holy Land where Jesus Christ -- the messiah or anointed one -- was born, preached, and offered himself as the ultimate sacrifice. Under the Greeks and Romans, it was the province of Judea, a name which hearkened back to the biblical kingdom of Judah. After the Bar-Kokhba revolt ended in 135 C.E., Hadrian renamed the province Syria-Palestina, reviving the memory of the long-vanished kingdom of Philistia. Under early Islamic rule the military district (jund) of Filastin was part of the province of Greater Syria (Arabic Bilad al-Sham). In this book, the term Palestine is used to denote the area encompassing the modern state of Israel, the Hashemite kingdom of Jordan, and the Palestinian territories"--